Gadai Berantai dalam Sorotan Hukum Islam: Studi Kasus di Desa Jaddung, Pragaan, Sumenep - Efaulamanah; Paisun (Santara: Journal of Islamic Law and Humanity, 2025)
This study examines the wisdom contained in the repetition of the verse "Waylu Yawmaiz li al-Mukazzibin" in Surah al-Mursalat using Ferdinand de Saussure's semiotic approach. The purpose of this study is to provide new insights into the meaning of the repetition of verses in Surah al-Mursalat. This repetition occurs ten times and is the main focus of this study, which is considered a sign from Allah containing important messages. To reveal this meaning, a semiotic approach is used with Saussure's dyadic theory (two elements). This study uses a library research method with descriptive analytical data presentation. The primary data sources used are Surah al-Mursalat and Ferdinand de Saussure's work, Course in General Linguistics, which has been translated into Indonesian. The results of the research show that: a) The repetition of the verse in Surah al-Mursalat functions as an affirmation and reinforcement of the warning for those who lie, b) The repetition of "Waylu" contains a threat for people who reject the teachings of Allah and the Day of Judgment, and provides a reward for those who are pious, c) The repetition of "Waylu" together with "al-Mukazzibin" reminds us not to lie and deny Allah's decrees, d) The wisdom contained in the Surah al-Mursalat reminds us of the retribution for people who deny the teachings of Allah and the Day of Judgment, as well as being a motivation to do good